Adult Onset Epilepsy and History of Childhood Febrile Convulsions: A Retrospective Study - Sardar, MH; Howlader, MAR; Hossain, MZ (Journal of Dhaka Medical College, 2010)
Objective: To assess the association between adult -onset epilepsy and history of childhood febrile convulsions (CFC) and determine the types of epilepsy which develop after CFC Design: A retrospective study. Study period: January 2008 to December 2008. Place of study: Epilepsy Clinic of the Department of Neurology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Materials & Methods: 106 consecutive adult (age>13 years) patients with adult onset epilepsy receiving treatment from Epilepsy Clinic of the Department of Neurology of BSMMU, Dhaka were the sample of this study. Records of these patients were reviewed & the patients & their family members were interviewed to assess the medical history. The data obtained from the records and the interviews formed the basis of this study. Chi-Square test was applied to analysis the data. Results: Results of interview and records of 92 patients were analyzed. Of the 106 patients 14 patients were excluded from this study for the reasons of missing reliable data of the CFC episodes (9), secondary epilepsy due to intracerebral space occupying lesions (ICSOL) (1), history of head injury (1) & meningoencephalitis (3). Thirty one (33.7%) of the remaining ninety two patients had history of CFC in the childhood (71% male, 29% female). Partial epilepsies were significantly associated with history of CFC [Odds Ratio : 3.29; (95% CI 1.30-8.06), (c2=5.49, df=1, p<0.012)] when compared to other epilepsies and epilepsy syndromes. An initial unprovoked simple partial seizure was also significantly associated with a positive history of CFC [Odds Ratio : 8.05; (95% CI 2.88-22.45), (c2=15.86, df=1, p<0.001)]. Conclusion: Partial epilepsies seem to be associated with a history of CFC in childhood. The mechanism & pathophysiology of association between CFC and epilepsy in affected probands requires further investigations. Identification of the basic defect in relation to CFC & epilepsy may have important implication for the prevention of adult- onset epilepsy in patients with history of CFC. But the risk of epilepsy after febrile convulsions is much less than reported in many hospital studies & if febrile convulsion causes brain damage that leads to epilepsy later, this is a rare occurrence. Key words: Generalized epilepsy; partial epilepsy; febrile convulsion; afebrile seizures; genetic. DOI: 10.3329/jdmc.v18i1.6307 J Dhaka Med Coll. 2009; 18(1) : 54-57